Xanomeline Protects Cortical Cells From Oxygen-Glucose Deprivation via Inhibiting Oxidative Stress and Apoptosis - Xin, Rujuan; Chen, Zhongjian; Fu, Jin; Shen, Fuming; Zhu, Quangang; Huang, Fang (Frontiers in Physiology, 2020)
Xanomeline, a muscarinic acetylcholine receptor agonist, is one of the first compounds that was found to be effective in the treatment of schizophrenics and attenuating behavioural disturbances of patients with Alzheimer’s disease (AD). However, its role in ischaemia-induced injury due to oxygen and glucose deprivation (OGD) remains unclear. Primary rat neuronal cells were exposed to OGD and treated with xanomeline. The effects of xanomeline on apoptosis, cell viability, lactate dehydrogenase levels, and reactive oxygen species (ROS) were determined using an Annexin V Apoptosis Detection Kit, a non-radioactive cell counting kit-8 (CCK-8) assay, colorimetric LDH cytotoxicity assay kit, and a dichloro-dihydro-fluorescein diacetate (DCFH-DA) assay, respectively, and the expressions of Sirtuin 1, haem oxygenase-1 (HO-1), B-cell lymphoma 2 (Bcl-2), poly ADP-ribose polymerase (PARP), and hypoxia-inducible factor  (HIF-1) as well as the level of phosphorylated kinase B (p-Akt) were determined by Western blotting. Compared with the control, xanomeline pretreatment increased the viability of isolated cortical neurons and decreased the lactate dehydrogenase release induced by OGD. Compared with OGD-treated cells, xanomeline inhibited apoptosis, reduced ROS production, attenuated the OGD-induced HIF-1 increase and partially reversed the reduction of HO-1, Sirtuin-1, Bcl-2, PARP and p-Akt induced by OGD. In conclusion, xanomeline treatment protects cortical neuronal cells possibly through the inhibition of apoptosis after oxygen-glucose deprivation.